Transformation Strategy: Indonesian National Police in Coordinating Crime in The Digital Era - Yustinus Bowo Dwinugroho (International Journal of Integrated Science and Technology, 2024)
The Indonesian National Police (POLRI) has the authority to handle crimes regulated by several laws, including Law no. 2 of 2002 concerning the National Police of the Republic of Indonesia, which is the basis for carrying out their duties in maintaining security and public order, enforcing the law, and providing protection and services to the community. The digital era has brought significant changes in various aspects of life, including security and law enforcement. Advances in information and communication technology not only open up new opportunities but also give rise to complex challenges such as cybercrime. This article analyzes POLRI's strategic transformation in responding to digital crime challenges. Through organizational restructuring, increasing personnel capacity, adopting advanced technology, and collaborating with various stakeholders, POLRI is trying to tackle cybercrime more effectively. This study uses a normative juridical approach and combines various theories to provide insight into the development of law enforcement in the digital era and the strategies implemented by POLRI in dealing with digital crime.